Heavy Metals Contamination of Cadmium and Chromium and Safety level for Consumption of Blood clam (Anadara granosa) at the Tallo River Estuary, Makassar City - Abdul Gafur; Habo Abbas, Hasriwiani (HIGIENE: Jurnal Kesehatan Lingkungan, 2022)
Abstract Heavy metal contamination can accumulate in seawater, sediments and marine life that live in it. Marine biota such as Blood clams (Anadara granosa ) contaminated with heavy metals exceeding the allowable threshold will endanger health if consumed by humans. This study aims to determine the content of heavy metals in blood clams (Anadara granosa ) in the Tallo River. Sampling was carried out at four blood clam collection stations in Tallo in June 2021. The results showed that the cadmium content in all sampling locations was abnormal with high cadmium content in each sample location ranging from 0.7671 mg / Kg-0.7942 mg / Kg. The content of heavy metal Cadmium in Blood Shells at all sampling stations was still above the permitted standard of 0.05 mg / kg according to WHO / FAO. The chromium content in blood clams showed that the high chromium content at station 3 was 11.4525 mg / Kg. This level exceeds the maximum limit of metal contamination in food that has been set by FAO / WHO (1979), which is 0.1 mg / Kg for metal chromium (Cr). At stations 1,2 and 4, the chromium content in the Anadara granosa Blood clam in the Tallo River is low. The value of the analysis results at the three stations was always below the limit of the AAS device, namely <0.01 mg / kg. This value is far below the quality standard set by FAO / WHO, which is 0.1 mg / kg. The low chromium content in Anadara granosa shells can be caused by the low chromium content itself in water and sediment. The analysis of the safe limits for consumption of green Blood clam contaminated with heavy metals carried out in this study showed that the good blood clams in the Tallo River were still safe to consume up to 1 kg / week in adults with an average body weight of 60 kg. Keywords : Blood clam, Cadmium (Cd), Chromium (Cr), Safety level for Consumption